Political, Military and Technical Cooperation of the Republic of Uzbekistan in the Framework of the Shanghai Cooperation Organization - Galiullin, Marat Zufarovich; Gumarov, Farkhad Linarovich; Kadyrov, Ramil Rashitovich; Kamaletdinova, Elvira Imbelevna (Cuestiones Políticas, 2020)
The article is devoted to the analysis of the main vectors of technical-military cooperation of the Republic of Uzbekistan within the framework of the Shanghai Cooperation Organization (SCO) in the Central Asia region. The SCO is widely believed to have been part of the Asian version of the North Atlantic Bloc and represents an organization with many areas of activity, where the technical-military cooperation of member countries plays an important role. The main objectives of the organization are to promote peace and stability in one more context, book the development of terrorism, separatism, extremism and drug trafficking, economic cooperation and energy partnership, cooperation and scientific. In made or use of the method anzé of systemic. It is concluded that cooperation in the technical-military field will provide the opportunity for the race to have a greater influence on global political and economic situations, without being abstracted solely from the tasks of the SCO, such as the mutual union of forces of major international organizations. The organization referred to will be in the resolution of various problems, both regionally and globally, to the extent that the talós objectives are consolidated and achieved.